2014
DOI: 10.1021/es500833z
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Transport of Phenanthrene and 1-Naphthol by Colloidal Graphene Oxide Nanoparticles in Saturated Soil

Abstract: With the increasing production and use of graphene oxide, the environmental implications of this new carbonaceous nanomaterial have received much attention. In this study, we found that the presence of low concentrations of graphene oxide nanoparticles (GONPs) significantly enhanced the transport of 1-naphthol in a saturated soil, but affected the transport of phenanthrene to a much smaller extent. The much stronger transport-enhancement effect on 1-naphthol was due to the significant desorption hysteresis (bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(52 citation statements)
references
References 40 publications
3
49
0
Order By: Relevance
“…This is because the presence of Cu 2+ increased the ζ-potential (less negative) and the hydrodynamic diameter (Dh) of GO (Table 1), and subsequently reduced GO transport in porous media, which is in accordance with the literature [18,21]. Likewise, Qi et al [37] demonstrated that Cu 2+ ions increased the aggregation of GO, thereby generally increasing the transport-enhancement capability of GO. In the presence of GO, the breakthrough of total ( Figure S3a), dissolved ( Figure S3b), and GO-facilitated (GO-F) Cu (Figure 4b) followed the same trend, exhibiting decreased migration and even retardant behavior as ω increased from 0 to 0.45, compared to sole Cu 2+ transport in the column ( Figure S4).…”
Section: Cotransport Of Cu With Gosupporting
confidence: 84%
“…This is because the presence of Cu 2+ increased the ζ-potential (less negative) and the hydrodynamic diameter (Dh) of GO (Table 1), and subsequently reduced GO transport in porous media, which is in accordance with the literature [18,21]. Likewise, Qi et al [37] demonstrated that Cu 2+ ions increased the aggregation of GO, thereby generally increasing the transport-enhancement capability of GO. In the presence of GO, the breakthrough of total ( Figure S3a), dissolved ( Figure S3b), and GO-facilitated (GO-F) Cu (Figure 4b) followed the same trend, exhibiting decreased migration and even retardant behavior as ω increased from 0 to 0.45, compared to sole Cu 2+ transport in the column ( Figure S4).…”
Section: Cotransport Of Cu With Gosupporting
confidence: 84%
“…2). 52,106,107 CNP attachment generally decreases with increasing negative surface charge. Biochar-derived pCNPs, which contain the most O-functional groups and negative surface charge could therefore form more mobile pCNPs than less oxidized pCNPs.…”
Section: Transport Of Cnps In Porous Mediamentioning
confidence: 99%
“…For instance, oxidation of CNPs can result in negatively charged contaminants being repulsed electrostatically from the negatively charged CNP surfaces. 11,94 However, polar compounds sorbed to CNPs by hydrogen bonds will become more strongly bound with an increase in surface O-functional groups (e.g., following oxidation of the CNPs) 107 and sorption can decrease with the disappearance of these functional groups (e.g., following reduction of the CNPs). 11 Such enhanced or inhibited polar interactions between polar contaminants (e.g., 1-naphthol) and CNPs can then determine the extent of facilitated transport of contaminants by CNPs.…”
Section: Effect Of Cnp Surface Chemistry On Contaminant Bindingmentioning
confidence: 99%
“…Colloids can also enhance the transport of dissolved contaminants in groundwater via their sorption onto colloid surfaces. Colloid‐facilitated transport has been studied for a wide range of contaminants including radionuclides [e.g., Kersting et al ., ; Novikov et al ., ], hydrocarbons [e.g., Qi et al ., ], and pesticides [e.g., de Jonge et al ., ; Sprague et al ., ]. Research in this area includes modeling the reduction in contaminant retardation [ Corapcioglu and Jiang , ; Johnson et al ., ; Flury and Qiu , ].…”
Section: Introductionmentioning
confidence: 99%